Rate of forgetting is independent from initial degree of learning - Rivera Lares, Karim (The University of Edinburgh, 2022)
Research on forgetting has extensively explored factors that modify the rate at which information is forgotten. However, the question of whether initial degree of retention influences the rates of forgetting has been neglected. Despite the scarcity of studies on the subject, it is frequently assumed that the rate of forgetting depends on initial degree of learning. Under this assumption, experiments that compare rates of forgetting between groups use matching procedures during encoding which add confounding variables. The main aim of this thesis was to investigate if this assumption is justified. A classic study by Slamecka and McElree (1983) found parallel forgetting curves for different initial degrees of learning in three experiments. They varied the level of initial acquisition across groups by exposing participants to a different number of study trials. Using different types of tests for each experiment, from semantic recognition to cued recall, they consistently found that more repetitions increased retention, which decreased over time. Importantly, they found that forgetting rates were independent from initial degree of learning. The first objective of this thesis was to explore whether forgetting rates vary as a function of different initial degrees of learning. Expanding from Slamecka and McElree (1983, Experiment 3), in Experiments 1 to 4, I used a list of 36 sentences, and tested them via cued recall at three retention intervals. These experiments varied the modality of presentation, the language used for the sentences, and the length of the retention intervals. The second objective was to investigate the relationship between initial degree of learning and forgetting rates as a result of ageing (Experiments 5 and 6). Both younger and older adults were exposed to four study trials of a list of 36 (Experiment 5) or 30 (Experiment 6) sentences. Memory performance was tested via cued recall at three retention intervals (30 s, 1 hr, and 1 day), using a different third of the sentences to-be-remembered at each retention interval. The third objective was to explore the relationship between initial degree of learning and forgetting rates of non-verbal material. Rates of forgetting can differ depending on some qualities of the material that make it more or less memorable. Most verbal material can be rehearsed, and although measures are taken to prevent participants from rehearsing between tests, it cannot be guaranteed that participants will not engage in rehearsing. In contrast, non-verbal auditory material is less able to be rehearsed. In Experiments 7 and 8, I explored the relationship between forgetting rates and initial degree of learning, using novel piano music excerpts. Experiment 7 was carried out in person and Experiment 8 was carried out online. Overall, the results of experiments demonstrated that forgetting rates are independent of initial degree of learning, whether this initial difference in performance is acquired by experimental manipulations such as the number of exposures to the material, or by natural occurring circumstances such as normal ageing. These findings are of practical importance for future studies which use cross-group comparisons (e.g., studies of forgetting in clinical populations).
Keywords: long-term memory; repeated testing; initial degree of learning; long-term forgetting; forgetting